The inflammatory mechanisms in schizophrenia - ARICIOĞLU, FEYZA (AVES PRESS LTD, 2015)
Schizophrenia is a serious mental illness that affects approximately 1% of the population worldwide, with chronic symptoms and significant impairment in psychosocial functioning. Interactions between genetic susceptibility and environmental stressors at the early stages of life, subsequently neurodegeneration process are important in the development of schizophrenia. Current approaches suggest that cytokines might have a role in the development of several psychiatric disorders, including schizophrenia. Uncontrolled activity of proinflammatory cytokines and microglia can induce schizophrenia in tandem with genetic vulnerability and neurotransmitter dysfunctions. Microglial activation induced by pro-inflammatory cytokines in central nervous system is responsible for the initiation and proceeding of inflammatory process and consequently developing neurodegeneration. Here in this review, we aimed to provide an overview to the latest findings related to the cytokines-mediated peripheral and central immune responses in the development of schizophrenia.
Keywords: Schizophrenia; cytokine; neuroinflammation